Differences in growth in prepubertal children with definite growth hormone deficiency, short stature unresponsive to stimulation tests, and idiopathic short stature treated with recombinant human growth hormone: a retrospective study - Tamaro, Gianluca; Lanzetta, Maria Andrea; Carlsson, Martin Ove; La Torre, Daria; Tornese, Gianluca (Frontiers in Endocrinology, 2025)
IntroductionGrowth hormone stimulation tests are crucial in diagnosing growth hormone deficiency (GHD) in children; however, their limited reliability and inconsistent thresholds pose diagnostic challenges. A proposed subclassification distinguishes definite GHD (dGHD), short stature unresponsive to stimulation (SUS), and idiopathic short stature (ISS). This study aims to assess whether these categories are distinguishable at baseline and differ in response to recombinant human growth hormone (rhGH) therapy, particularly in terms of near adult height (NAH) outcomes.MethodsThis retrospective cohort study analyzed data from 3,939 prepubertal children in the KIGS (Pfizer International Growth Database) who received rhGH therapy and reached NAH. Patients were classified into three groups: dGHD (GH peak <8 ng/mL with identifiable genetic, functional, or anatomical causes), SUS (GH peak <8 ng/mL without an identifiable cause), and ISS (GH peak ≥8 ng/mL). Multivariable regression analyses assessed the association of various factors with NAH outcomes.ResultsChildren with SUS showed baseline differences from those with dGHD but responded similarly to rhGH, with a height SDS increase of 0.13 for SUS and 0.12 for dGHD. In contrast, ISS children exhibited a smaller response (0 SDS increase). At the end of rhGH treatment, 74% of dGHD and SUS patients achieved a normal height (≥-2 SDS), compared to 65% of ISS patients. The most significant predictors of NAH included height at treatment initiation and mid-parental height, particularly in ISS patients.ConclusionDespite initial differences, children with SUS responded similarly to rhGH as dGHD patients, while ISS patients had a less favorable response. These findings support the importance of subclassifying short stature conditions to refine diagnostic processes, enhance treatment approaches, and improve growth outcome predictions.